The Influence of Teamwork on Employee Performance with the Work Environment as an Intervening Variable at the BPJS Employment Office, South Sumatra - Rahmad Hidayat Batubara; Mesra B (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This research aims to see the effect of teamwork on employee performance with the work environment as an intervening variable at the South Sumatra BPJS Employment Office, the type of research used is quantitative, this research was conducted at the South Sumatra BPJS Employment Office, the population of this study was 120, research sample This is 92 using the Slovin sampling technique, the way to collect data is using a questionnaire, the data used is primary data, the research model used is PAHT analysis and the research measuring tool uses SAMRT PLS version 3. The results of this research are as follows: Work Environment has a positive and significant effect on employee performance with an original sample value of 0.385 and a P value of 0.000. Teamwork has a positive and significant effect on employee performance with an original sample of 0.544 and ap value of 0.000. Teamwork has a positive and significant effect on the Performance Environment with an original sample value of 0.931 and ap value of 0.000. Teamwork has a positive and significant effect on employee performance through the work environment with an original sample value of 0.359 and ap value of 0.000.